THE WORD AND EMOTIONS. DISCURSIVE INTERACTION BUILDING AS HYDROTHERAPY STRATEGY IN PHYSICAL, EMOTIONAL AND SOCIAL RECOVERY IN PATIENTS WITH PARKINSON DISEASE AND STROKE (Fiep Bulletin - online, 2013)
"Sometimes a word can be better than a pill" it was the speech which stimulated me to do this work. Words highlighted by a lady suffering from Parkinson's disease while waiting for her hydrotherapeutic treatment session and talked to me. So, I felt challenged to investigate how the words, beyond the power of healing, are steps which drive the individuals to achieve their social space, in a world where the standards of beauty and perfection separate the "able" and "disable". In order to accomplish this study, two interviews were conducted, one with the client with Parkinson's disease and another one with a client recovering from stroke, during the hydrotherapy sessions. They highlight the important role of the hydrotherapist, Albanize, in their physical and social recovery, through her discourse in rebuilding self-esteem, overcoming, social reintegration and achieving dreams. Albanize declares that her words, in the first conversation she has with her clients, are the first step to reach them and relieve them from the pain of the soul, which is loneliness. Albanize awakens perceptions which activate the necessary neurons for the construction of emotions which elevate the self-esteem and command the body's reactions in physical, emotional and social recovery responses. Albanize adequate her words to each different life story that integrates her work in a zealous and no stopping care.
Keywords: hydrotherapy; word; self-esteem.